Development of flipped classroom module based on student created videos to improve hots - Azin Taufik; Aulia Barkah Safitri; Rahayu Syafari (Universitas Muhammadiyah Lampung, 2026)
Higher Order Thinking Skills (HOTS) are essential competencies that should be fostered in mathematics education to enable students to analyze, evaluate, and solve problems critically. However, students' HOTS remain relatively low due to teacher centered instruction, low learning motivation, and limited learner autonomy. This condition was also identified among eighth grade students at SMPN 5 Kuningan. The results of the preliminary test on statistics indicated that students were able to calculate the mean, median, and mode but were not yet able to analyze, evaluate, or provide appropriate reasoning when solving problems. Although numerous studies have examined the flipped classroom approach and the student created video strategy separately, research integrating both into a teaching module to enhance HOTS in statistics instruction remains limited. Therefore, this study aimed to develop a student created video-based flipped classroom teaching module, evaluate its validity and practicality, and examine its effectiveness in improving students' HOTS. This study employed a Research and Development (R&D) approach using the ADDIE model involving 20 eighth-grade students at SMPN 5 Kuningan. Data were collected through observations, questionnaires, and tests and were analyzed using percentage analysis and the normalized gain (N-Gain) test. The results showed that the developed module was highly valid, with validity scores ranging from 82.00% to 87.69%, and highly practical, as reflected in the positive responses from teachers (85.42%) and students (82.05%). Furthermore, the implementation of the module improved students' HOTS, with an N-Gain score of 0.52, which was classified as moderate. These findings indicate that the student created video based flipped classroom teaching module is a valid, practical, and effective instructional resource for supporting statistics instruction and promoting the development of Higher Order Thinking Skills.